1998
DOI: 10.1097/00006534-199807000-00033
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of Facial Aging

Abstract: Facial aging is a biological phenomenon. Skin properties change with time, and gravity and facial expressions exert mechanical deformation. Knowledge of these alterations may suggest ways to reverse them by identifying the corresponding distortional forces. The aim of this study was to determine a pattern of change for parameters of the face during the aging process, based on the numerical fitting of measures from a sample of patients. The first aspect of this study was to define adequate facial parameters and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 1 publication
0
14
0
1
Order By: Relevance
“…The last age class (men and women between 31-40 years of age) should represent the beginning of aging, and correspond to "middle-aged adults" (Gualdi-Russo, 1998;Pitanguy et al, 1998;Ferrario et al, 1999aFerrario et al, , 2001a.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The last age class (men and women between 31-40 years of age) should represent the beginning of aging, and correspond to "middle-aged adults" (Gualdi-Russo, 1998;Pitanguy et al, 1998;Ferrario et al, 1999aFerrario et al, , 2001a.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in women were less evident; apparently, females retain more of their childhood appearance in shape than males (Enlow, 1990). This finding is limited to selected facial landmarks and does not consider the actual appearance of the soft tissues (Pitanguy et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study could potentially be useful for plastic surgeons in various cosmetic procedures if the parameters a and b obtained could be connected to the ratio between the original thickness, H , and the thickness after expansion, t [Pitanguy et al 1998]. When we combined the results in this manner, it became clear that the parameters of the first patient that received skin expansion of the scalp did not fit well with the other three patients, as seen in Figure 5.…”
Section: 4mentioning
confidence: 92%
“…The effects of the round-lifting technique were studied by analyzing the mechanical forces applied and the displacements produced. 21,22 The method of finite elements was employed and, by means of computers, the relevant equations were defined. Human skin was modeled as a pseudoelastic, isotropic, noncompressible and homogeneous membrane, and a computational study of the fields of displacement and the forces ap- plied to the flaps during a rhytidoplasty demonstrated that pulling on the skin creates areas of tension that can be either negative or positive.…”
Section: Figurementioning
confidence: 99%